PEMBERDAYAAN MASYARAKAT DALAM MENINGKATKAN KUALITAS HIDUP LANSIA PANTI SOSIAL TRESNA WERDHA BUDI SEJAHTERA II MELALUI PERAWATAN KESEHATAN GIGI DAN MULUT DI KELURAHAN SUNGAI PARING MARTAPURA - Kisworo Utami, Naning; Amperawati, Metty; Nurwati, Bunga; Yulianty, Yulianty; Nurhaliza, Minadila; Salsabila, Syifa (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2025)
Dental and oral health care for the elderly is an important aspect in improving their quality of life. According to the 2018 Riskesdas report, the largest proportion of dental problems in Indonesia is tooth decay/cavities/pain (45.3%). Meanwhile, the prevalence of dental caries in Indonesia is 88.8% with the prevalence of root caries at 56.6% (Riskesdas, 2018). The goal of community service is to carry out : Community Empowerment to Improve the Quality of Life of the Elderly at the Social Welfare Home for the Elderly “Budi Sejahtera II” Through Dental and Oral Health Care in Sungai Paring Village, Martapura. The total number of residents is 70 elderly people located at the Social Welfare Home for the Elderly “Budi Sejahtera II” Martapura, Banjar Regency, South Kalimantan Province. In this community service, the respondents are 30 elderly individuals (25 elderly and 5 staff members from the home). The results obtained show that there are 6 respondents (24.0%) with ≥ 10 teeth, 11 respondents (44.0%) with 6-10 teeth, and 8 respondents (32.0%) with ≤ 6 teeth. Meanwhile, there are 16 respondents (64.0%) without caries and 9 respondents (36.0%) with no caries or who have lost their teeth (edentulous). It is recommended to have dental care by getting dental fillings either at the nearest community health centre or hospital. Providing education and examining the dental and oral hygiene of the elderly through integrated health services and mobile health centres can be an effort for early detection and prevention of dental and oral health problems. This can help reduce the incidence of dental pain and tooth loss among the elderly. Keywords : Community Empowerment - Dental Caries – Elderly